Analysis Of The EU Cybersecurity Act Under The Theory Of Neoliberal Institutionalism - Safrida Alivia Sri Ananda; Ika Riswanti Putranti; Andi Akhmad Basith Dir (Arena Hukum, 2022)
Wannacry Ransomware epidemics have attacked several high-profile companies in European Union creating an EU-wide cybersecurity crisis in the digital economy and social order. In response, European Union established an appropriate regulation in cybercrime namely The Cybersecurity Act. The Act as an international regime does not only gives a permanent mandate that strengthens European Union Agency for Network and Information Security (ENISA) but also establishes The EU Cybersecurity Certification Scheme in order to increase cybersecurity and build cyber resilience in the European Union Digital Single Market. This paper investigates how does the Cybersecurity Act as a business law in maintaining cybersecurity aspect on the European Union Digital Single Market through the theory of neoliberal institutionalism as a framework of thinking. After a series of conduction of literature reviews, this research argues that The Cybersecurity Act would be an appropriate regulation in dealing with the cybersecurity crisis in the digitalized market order. The standardization in The EU Cybersecurity Certification Scheme regulated by The Cybersecurity Act would improve cybersecurity and build cyber resilience in the European Union Digital Single Market.